Occurrence of Zaprionus indianus (Diptera: Drosophilidae) in Agudo, Rio Grande do Sul, Brazil - Batistella Pasini, Mauricio Paulo; Link, Dionísio (EntomoBrasilis, 2012)
This work has the first record of Zaprionus indianus Gupta (Diptera: Drosophilidae) found in the rural area of Agudo in the state of Rio Grande do Sul, Brazil. The adults were first found in plums (Prunus salicina Lindl). Subsequently it was found in mature figs (Ficus carica L.) in two orchards. In the first orchard about 80% of the collected figs were infested by Z. indianus. In the second orchard, 50% of the figs cv. “Pingo de mel” and 80% of the figs of cv. “Roxo de Valinhos” were infested. On these collected figs a total of 1364 adult insects emerged. Figs of cultivar “Roxo de Valinhos” had higher adult emergence number. Besides being present in residues of the figs, Z. indianus was observed flying over debris from Syagrus romanzoffiana (Cham), Cucumis melo L., Citrullus vulgaris Schrad. and Vitis vinifera L., associated with other Drosophilidae. These findings indicate that measures for monitoring and pest control should be adopted in the county to ensure high quality figs. Ocorrência de Zaprionus indianus (Diptera: Drosophilidae) em Agudo, Rio Grande do Sul, Brasil Resumo. Este trabalho faz menção ao primeiro registro de Zaprionus indianus Gupta (Diptera: Drosophilidae) encontrado na zona rural do município de Agudo, no estado do Rio Grande do Sul, Brasil. Os adultos da mosca foram encontrados primeiramente em frutos de ameixa (Prunus salicina Lindl) posteriormente em figos maduros (Ficus carica L.) em dois pomares. No primeiro pomar cerca de 80% dos figos coletados apresentaram ataque de Z. indianus e, no segundo pomar 50% dos figos da cv. “Pingo de mel” e 80% da variedade “Roxo de Valinhos” foram infestados. No período correspondente a emergência dos adultos, coletou-se um total de 1364 indivíduos. Os figos da cv “Roxo de Valinhos” apresentaram maior emergência de adultos. Além de estar presente em restos culturais de figo, Z. indianus foi visualizada sobrevoando restos culturais de Syagrus romanzoffiana (Cham.), Cucumis melo L., Citrullus vulgaris Schrad. e Vitis vinifera L., associada a outros drosofilídeos. Ressalta-se que medidas de monitoramento e controle da praga deverão ser adotadas no município para garantir figos de alta qualidade e sadios.